The Impact of Multilingualism on Vocabulary Processing and Language Comprehension in Young Adults - Ade Fitria Fatimah (Sekolah Tinggi Agama Islam Kuningan, 2025)
Multilingualism is increasingly common among young adults, providing a variety of cognitive impacts that affect vocabulary processing and language comprehension. Although multilingualism has benefits for cognitive flexibility, complex cognitive processes can result in challenges in proper word selection as well as language comprehension, especially when switching languages. This study aims to explore how multilingualism has an impact on vocabulary processing and language comprehension in young adults, with a focus on the phenomenon of language interference. Using a qualitative method with a case study approach, data were collected through in-depth interviews with a group of young adults who mastered more than one language. Thematic analysis was applied to identify key patterns in their language processing experience. The results showed that multilingual young adults often face